A theoretical insight for solvent effect on myoglobin assay of - Ustun, E; Demir, S; Coskun, F; Kaloglu, M; Sahin, O; Buyukgungor, O; Ozdemir, I (2016)
Novel tetracarbonyl complexes of type W(CO)(4)L-2 (L: 4-chlorobenzylimidazoline; 4-methylbenzylimidazoline; 3,5-dimethylbenzylimidazoline; 2,4,6-trimethylbenzylimidazoline; 2,3,5,6-tetramethylbenzylimidazoline) were synthesized. Then newly synthesized novel compounds were characterized by IR, H-1 NMR, C-13 NMR and LC-MS. The characterizations of two of the complexes have also been confirmed with single crystal X-Ray diffraction and OFT optimization results of these complexes have been compared with single crystal results. We have investigated the solvent effect on the structure and metal-to-ligand charge transfer (MLCT) transitions with OFT/TDDFT calculations with ORCA package program with BP86 functional. (C) 2016 Elsevier B.V. All rights reserved. C1 [Ustun, Elvan] Ordu Univ, Fac Art & Sci, Dept Chem, TR-52209 Ordu, Turkey. [Demir, Serpil; Coskun, Feyzullah; Kaloglu, Murat; Ozdemir, Ismail] Inonil Univ, Dept Chem, Fac Sci, TR-44280 Malatya, Turkey. [Sahin, Onur] Sinop Univ, Sci & Tech Res Applicat & Res Ctr, TR-57000 Sinop, Turkey. [Buyukgungor, Orhan] Ondokuz Mayis Univ, Dept Phys, TR-55139 Samsun, Turkey.